1937
DOI: 10.3181/00379727-36-9345
|View full text |Cite
|
Sign up to set email alerts
|

Gonadotropic Hormones of the Hypophysis of the Turkey.

Abstract: E'rot)i t h p Zooloprccil L n b o r t r t o~y , Sttrtc University of Iowa.Relatively little \ I ork has been done in the past on the hypophysis of birds. Benoit' obtainetl evidence for the presence of gonadotropic hormones in hypophyses of sexually active ducks but not in those of inacti\-e ones. Similarly Riddle and Schooley2 found no effects from implanted hypophyses of pigeons less than 1.8 months old, while those of mature pigeons gave definite indication of the presence of some gonad stimulating principle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1937
1937
1971
1971

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Gonadal maturation and ovdation are &Is0 d i r e c t l y controlled by the hypophyseal gonadotrophic hormones (29).…”
Section: Most Female Birds L a Y One Egg Approximately Ovulation Occursmentioning
confidence: 99%
“…Gonadal maturation and ovdation are &Is0 d i r e c t l y controlled by the hypophyseal gonadotrophic hormones (29).…”
Section: Most Female Birds L a Y One Egg Approximately Ovulation Occursmentioning
confidence: 99%
“…The pituitary of birds contains gonadotropic hormone capable of stimulating the mammalian ovary fowl pituitary, ovulation in the rabbit, or ovarian hypertrophy in the normal or hypophysectomized rat; Witschi, Stanley, and Riley, 1937, turkey pituitary, ovarian hypertrophy in the normal or hypophysectomized rat). Leonard concluded that the fowl's pituitary contains luteinizing hormone as well as the hormone stimulating the adrenal cortex.…”
Section: The Biology Of the Gonadotropic Hormones In Vertebratesmentioning
confidence: 99%